2021
DOI: 10.3390/met11010167
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Tool Coating and Cutting Parameters on Surface Roughness and Burr Formation during Micromilling of Inconel 718

Abstract: Surface roughness and burr formation are among the most important surface quality metrics which determine the quality of the fabricated parts. High precision machined microparts with complex features require micromachining process to achieve the desired yet stringent surface finish and dimensional accuracy. In this research, the effect of cutting speed (m/min), feed rate (µm/tooth), depth of cut (µm) and three types of tool coating (AlTiN, nACo and TiSiN) were analyzed to study their effect on surface roughnes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 83 publications
(114 reference statements)
3
9
0
Order By: Relevance
“…This, in turn, would lead to a rough application of the cutter on the workpiece, thereby leading to a lot of surface roughness. This finding is in agreement with the literature [50,51,[54][55][56]. The depth of cut, however, geometrically increased the surface roughness at 0.8 mm depth of cut.…”
Section: Effect Of Machining Parameters On Surface Roughnesssupporting
confidence: 93%
“…This, in turn, would lead to a rough application of the cutter on the workpiece, thereby leading to a lot of surface roughness. This finding is in agreement with the literature [50,51,[54][55][56]. The depth of cut, however, geometrically increased the surface roughness at 0.8 mm depth of cut.…”
Section: Effect Of Machining Parameters On Surface Roughnesssupporting
confidence: 93%
“…However, the CT under dry conditions shows better results between durations of 45s and 65s. This can be attributed to built-up edge formation in the CT under dry conditions, as shown in Figure 5 and Figure 6, which may reduce the contact between the tool and the workpiece and reduce the VBb [35]. At the end of machining, the size of the built-up edge may reduce, increasing the contact between tool and workpiece, which increases the VBb.…”
Section: Flank Wearmentioning
confidence: 99%
“…However, a small crater, built-up edge and chipping of the cutting edge are observed. The crater is mainly due to the chemical affinity of Nimonic-90 and tools [34,35]. A high temperature near the cutting edge imposes the welding between chip and tool even in the UAT, leading to the built-up edge and chipping adhesion.…”
Section: Crater Wearmentioning
confidence: 99%
“…Jing et al [ 13 ] investigated the performance of AlTiN-based composite coatings in dry end milling of hardened steel and found that AlTiN-based composite coatings performed well in reducing cutting forces, preventing adhesive wear and isolating cutting heat and were suitable for dry milling of hardened SKD11. It is possible to reduce surface roughness and improve surface quality using coatings by optimizing the coating film thickness [ 14 ] and cutting parameters [ 15 ]. The coating performance is influenced by process parameters such as bias voltage [ 16 ], arc current [ 17 ], substrate temperature [ 18 ] and gas flow rate [ 19 ] in the preparation of multi-layer composite coatings by arc ion plating process.…”
Section: Introductionmentioning
confidence: 99%